Flow Control by Slot Position and Noise Baffle in a Self-Recirculation Casing Treatment on an Axial Fan-Rotor. (11th January 2017) - Li, Xiangjun; Spence, Stephen; Chen, Hua; Chu, Wuli; Gibson, Lee
Abstract : To address the situations where the casing treatment needs to be used to stabilize axial compressors through strong recirculation, this paper initiated a CFD study to investigate how the flow could be suitably controlled in the casing treatment to minimize the efficiency penalty and increase the flow range. A counter-swirl self-recirculation casing treatment was first designed on a low speed axial fan rotor as a baseline case. Then three different slot positions and the influence of including the noise baffle were numerically studied. Based on the understanding of their coeffects, the shorter noise baffle was considered and it was found that the highest efficiency was achieved in the case of the upstream slot when the length of baffle was suitably adjusted to balance the incoming flow and recirculation. The largest flow range was achieved by locating the slot at the most downstream position and using a 50% length baffle since it suitably controlled the recirculating flow and relieved the separation at the low-span region. An optimization study showed that the optimum length of the baffle for efficiency was always larger than for the flow range. Both of the two optimum values reduce as the slot moves downstream.